The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7gc00896a
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization engineering – How to design advanced sol–gel systems for biocatalysis?

Abstract: An immobilization engineering approach using bioinformatics and experimental design tools was applied to improve the sol-gel enzyme entrapment methodology. This strategy was used for the immobilization of lipase B from Candida antarctica (CaLB), a versatile enzyme widely used even on the industrial scale.The optimized entrapment of CaLB in sol-gel matrices is reported by the response-surface methodology enabling efficient process development. The immobilized CaLBs characterized by functional efficiency and enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 56 publications
(15 reference statements)
0
39
0
Order By: Relevance
“…Also up to 90 °C, however, the ee (R)-2 values obtained with M540-PDE-PS were higher than those produced with Lipobond Lipase PS. It was already demonstrated that operational stability of immobilized lipases in continuous-flow kinetic resolutions at the optimum temperature are quite high and stationary reaction conditions could be maintained even for one week period [17,65,66].…”
Section: Comparison Of the Productivity And Selectivity Of Lipase Ps mentioning
confidence: 99%
See 1 more Smart Citation
“…Also up to 90 °C, however, the ee (R)-2 values obtained with M540-PDE-PS were higher than those produced with Lipobond Lipase PS. It was already demonstrated that operational stability of immobilized lipases in continuous-flow kinetic resolutions at the optimum temperature are quite high and stationary reaction conditions could be maintained even for one week period [17,65,66].…”
Section: Comparison Of the Productivity And Selectivity Of Lipase Ps mentioning
confidence: 99%
“…What is more, they are reusable, what is economically more sustainable, and the separation of immobilized biocatalyst from the reaction mixture is more easy. Various immobilization techniques have been developed, including adsorption, covalent binding, entrapment, encapsulation and cross-linking [17][18][19][20][21][22][23]. Selection of materials for immobilization has an effect on the properties of immobilized enzymes [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Even today -due to the extremely expanding requirements of biotechnologyenzyme and cell immobilization is a rapidly developing area. The main aims of immobilization strategies are the isolation, compartmentalization and stabilization of the valuable cells, cell organelles or enzymes with high biocatalytic activity [14][15][16][17][18]. Although several immobilization methods and carrier systems for cells or enzymes are based on similar methods (binding reactions and media, carrier materials etc.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Previous studies 15,[26][27][28] already stated the versatility of the sol-gel immobilization method and the possibility to ne tune the composition of the binary or ternary precursors mixture to achieve high activity and selectivity, but these studies were carried out on model secondary alcohols (1-phenylethanol or 2-alkanols). The present study demonstrates for the rst time the efficiency of the tailored binary and ternary sol-gel immobilized lipase preparates for the EKR of various heteroaromatic alcohols.…”
Section: 17mentioning
confidence: 99%
“…[10][11][12] When some protective additives (crown ether, isopropyl alcohol, etc) were used in the sol-gel immobilization process, for certain substrates a supplementary increase of the lipase activity in esterication and enzymatic kinetic resolution (EKR) processes was already reported. [13][14][15] Lipases are most frequently used for the synthesis of chiral intermediates by kinetic resolution in an immobilized form.…”
Section: -8mentioning
confidence: 99%